Variabel yang mempengaruhi motivasi dan kinerja pegawai pada kantor perpustakaan dan arsip daerah - Idhamsyah Idhamsyah; Zainal Ilmi; Dirga Lestari AS (Faculty of Economics and Business Mulawarman University, 2018)
Human Resource Management is a resource of Development to emphasize human being as the main actors of development having work ethic or working method that productive, creative, discipline, skilled, professional and master of science and technology with environment or natural surroundings, ability to manage and also interact with all forms of work. Organizations need a good performance of every human resource they have in order to better the community's assessment of the organization as well, so the organization also needs to take various actions in achieving the good performance generated by its employes. The purpose of this study is to analyze and determine the influence of Variables Affecting Employee Motivation and Performance. This research was conducted by taking the object of the Office of Library and Archives Region Office in Paser Regency, with a population of 40 employees. The theory used is the theory of human resource management, Competence, Experience, This study uses data taken directly from the sample by using a questionnaire system. The samples of the research are the employees of the Library and Archive Regional Office in Paser Regency with a total of 40 samples. The research model uses path analysis using SmartPLS as an analytical tool. From the result of the analysis test, it can be concluded that the competence variable (X1) has a significant and positive effect on the motivation (Y1), and on the performance (Y2), the experiential variable (X2) has a significant positive effect both on motivation (Y1) and performance (Y2) Compensation variable (X3) has a significant and positive effect on Motivation (Y1), and on Performance (Y2), and. And Motivation variable (Y1) have a significant effect on performance variable (Y2). Keywords: Performance, Motivation, Compensation, Competence